(untitled) (Bioagro, 2024)
In arid zones, salinity stress is one of the most predominant abiotic stresses which causes significant loses in agricultural production. The objective of this study was to evaluate the physiological and morphometric characteristics of Chenopodium ambrosioides L. to determine its tolerance to NaCl-stress. The experiment used a completely randomized design with five NaCl concentrations (0, 50, 100, 150 and 200 mM) with four replications per treatment of 15 plants each. The morphometric variables evaluated were dry weight of aerial part, dry weight of root, leaf area, length of root mass and total root length. The physiological variables were photosynthetic rate, stomatal conductance, intercellular CO2, transpiration rate, relative water content, water potential, and leaf temperature. The results showed that C. ambrosioides is a plant that tolerates up to 100 mM NaCl in relation to the dry weight of the aerial part, length of root mass and total root length. In relation to the physiological variables, the results showed the ability of epazote to tolerate up to 50 mM NaCl since the relative water content, photosynthetic rate, stomatal conductance, and intercellular CO2 decreased from 50 mM NaCl, while the transpiration rate decreased from 150 mM NaCl.